Increased in cyclooxygenase—2 immunoreactivity and DNA damage in hippocampus of rats infected by Trypanosoma evansi. (May 2016) - Baldissera, Matheus; Sagrillo, Michele; Sá, Mariângela; Peroza, Luis; Posser, Christopher; Brum, Gerson; Peres, Diulle; Mello, Adriana; Ferrão, Mirian; Souza, Carine; Silva, Aleksandro; Monteiro, Silvia
Abstract Cyclooxygenase-2 (COX-2) is one of the two isoforms of COX producing prostaglandins derived from arachidonic acid. COX-2 is the inducible isoform expressed in many cell types in response to cytokines and pro-inflammatory molecules. In brain, COX-2 is frequently associated with pro-inflammatory activities, and its increase is related to neurodegenerative processes in acute and chronic diseases. Thus, the aim of this study was to evaluate the COX-2 immunoreactivity and the frequency damage caused byT. evansi infection on days 5 and 15 post-infection (PI) in hippocampus cells, as well as the relationship with behavioral alterations. Decreased (p < 0.05) memory was observed in infected rats on days 5 and 15 PI. An increase in COX-2 immunoreactivity was observed in hippocampus of infected rats on day 15 PI (p < 0.05). Similarly, there was an increase in the frequency of damage in hippocampus of infected rats on days 5 and 15 PI (p < 0.05). This increment on COX-2 immunoreactivity may be associated with pro-inflammatory activities. Such activities are related to neurodegenerative alterations, as observed in histopathological analyses, and contribute to neurological pathophysiology of trypanosomosis.